Management of HIV-positive pregnant women: a Singapore experience - Loh, Michelle (2022)
INTRODUCTION: Perinatal transmission remains one of the important causes of transmission of the human immunodeficiency virus (HIV). Over the years, with better knowledge and awareness of HIV infection, the perinatal transmission rate has been significantly reduced. We previously reported on the pregnancy outcomes of HIV-positive mothers from 1997 to 2007 in our institution. This article aimed to review the standards of care of HIV-positive pregnant women since then. METHODS: A retrospective study reviewed 84 HIV-positive women who delivered in a tertiary centre from January 2008 to December 2015. Patient demographics and antenatal, intrapartum, postnatal and immediate neonatal data were analysed. RESULTS: A total of 97 deliveries with 98 neonates were recorded; 12 women delivered more than once, and there was one set of twins. The mean maternal age at diagnosis of HIV infection was 27.8 years. Of the study population, 63.1% of women were non-Singaporeans. 56 women were known to have HIV infection on presentation and 90.7% were on antiretroviral therapy during pregnancy. 88.7% of the women received intrapartum intravenous zidovudine, and 93.1% of women with detectable and 58.7% with undetectable viral load underwent Caesarean sections. All neonates were HIV-negative. CONCLUSION: The high standards of care for HIV-positive women have successfully reduced our perinatal transmission rate to zero.